(untitled) (Iranian Journal of Kidney Diseases, 2023)
Pediatric organ transplantation, specifically kidney transplant, has improved considerably in recent decades in Iran. Since infections are the most common cause of morbidity and mortality among transplanted children, pre-transplant vaccination is an effective preventive tool in this regard. In addition, administration of some vaccines is contraindicated in post- transplant period and the efficacy and immunogenicity of authorized vaccines may also be suboptimal in comparison to normal population. Therefore, pre-transplant period offers an outstanding chance to boost the immunization of this population. With regard to this population, it is imperative to establish a localized vaccination guideline, which can be used by nephrologists and other clinicians who are part of the transplant team, in Iran. Currently, such a local guideline for Iranian pediatric kidney transplant candidates is not available. The aim of this study is to provide a comprehensive overview of the existing vaccines recommended for these cases regarding the Expanded Program on Immunization (EPI) and available vaccines in Iran. In addition, general principles of vaccination, the use of specific vaccines as well as accelerated vaccination in this population are discussed in this article. This review could be a preliminary guide for preparing a comprehensive guideline for vaccination of this population in Iran. DOI: 10.52547/ijkd.7660